Factors affecting roe deer occurrence in a Mediterranean landscape, Northeastern Portugal - Torres, Rita Tinoco (2019)
The European roe deer population in Portugal is on the southwestern edge of its distribution. Understanding limiting factors that act on these populations enlightens both local aspects concerning their conservation and wider scale aspects of the species bioclimatic envelope, which is crucial for being better able to predict the impacts of environmental change. Accordingly, a survey was conducted to explore roe deer distribution in a 75,000 ha area located in Trás-os-Montes region, a Mediterranean landscape in the northeast of Portugal. Pellet-group counts were used to examine how roe deer distribution was related to habitat structure and composition, landscape structure, and human disturbance. The analysis considered two spatial scales: habitat patch and the wider landscape. At the patch scale, roe deer distribution was positively associated with high density of shrubs and with increasing distance from roads. At the landscape scale, roe deer distribution was negatively associated with spatial heterogeneity, namely mean shape index. Our findings suggest that landscape structure, vegetation composition and distance to roads are all important factors influencing roe deer distribution, highlighting the importance of multi-scale approaches.